IMPLEMENTASI PROGRAM PENDIDIKAN PROFESIONAL GURU (PPG) PENDIDIKAN AGAMA ISLAM DI UIN SYARIF HIDAYATULLAH JAKARTA - jejen musfah inning (Balai Penelitian dan Pengembangan Agama Jakarta, 2017)
The purpose of this article is twofold: 1) to analyze the implementation of the Professional Teacher Education (PPG) Program for Islamic Religious Education Teachers at the Faculty of Tarbiyah and Education Sciences (FITK) of the State Islamic University (UIN) Syarif Hidayatullah Jakarta, and 2) to analyze the teaching competence of PPG lecturers. This study used a qualitative approach and the data collection was done by using participatory observation, interview, and documentation. While data analysis used is the flow model of analysis, consisting of data reduction, data presentation, and conclusion. This study shows that not all PPG lecturers were good at teaching ability. Teaching methods are monotonous and not compliant with the character of students. The implementation of the PPG FITK has been running well, but there are some things that need to be improved such as the placement of teachers at all levels at MI, MTs, and MA, the communication between students and teachers, tutors, lecturers, and mentors, teaching courses seem still theoretical, and observation at the madrasah is unnecessary. Besides, there are other problems associated with the effectiveness of PPG as follows: the distance of participant's houses, teachers are still on duty at the school, so it distracted their focus, educational background that is not relevant to the PPG, and scholarships are often paid late. Keywords: Professional Teacher Education (PPG), Islamic Religious Education,UIN Syarif Hidayatullah